Do Financial Reporting Quality and Corporate Governance Have Simultaneous Effect? Evidence from Indonesian Manufacturing Companies - Arieftiara, Dianwicaksih; Utama, Sidharta (AKRUAL: JURNAL AKUNTANSI, 2018)
Financial reporting reflects transparency of the firm and if it could not explain the changes in shareholdersâ value in a timely manner; shareholders need additional monitoring mechanism. This study aims to investigate the effect of financial statementsâ quality on corporate governance mechanism and to examine the simultaneous effect between both. This study uses earnings timelines as a proxy of financial reportingâs quality; proportion of independent board and board size as proxies of corporate governance mechanism. Using Two Stage Linear Regression (TSLS) and samples consist of manufacturing companies listed on Indonesian Stock Exchange (IDX) in 2015, this study finds that earnings timelines have significant influence on board size; earnings timelines and proportion of independent board have the simultaneous effect; however, it fails to document the simultaneous effect of earnings timelines and ownership concentration. This study is the first that investigates the simultaneous effects of financial reporting quality and corporate governance.